Advances in Information and Computer Security 9th International Workshop on Security, IWSEC 2014, Hirosaki, Japan, August 27-29, 2014. Proceedings - Yoshida, Maki.; Mouri, Koichi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 9th International Workshop on Security, IWSEC 2014, held in Hirosaki, Japan, in August 2014. The 13 regular papers presented together with 8 short papers in this volume were carefully reviewed and selected from 55 submissions. The focus of the workshop was on the following topics: system security, threshold cryptography, hardware security, foundation, and encryption.
System Security -- Privacy-Friendly Access Control Based on Personal Attributes -- Are You Threatening my Hazards? -- Complicating Process Identification by Replacing Process Information for Attack Avoidance -- Kernel Memory Protection by an Insertable Hypervisor which has VM Introspection and Stealth Breakpoints -- Key Management for Onion Routing in a True Peer to Peer Setting (short paper) -- Threshold Cryptography -- Cheater Identifiable Secret Sharing Schemes Via Multi-Receiver Authentication -- Cheating Detectable Secret Sharing Schemes Supporting an Arbitrary Finite Field (short paper) -- Secure Multi-party Computation for Elliptic Curves (short paper) -- More Constructions of Re-splittable Threshold Public Key Encryption (short paper) -- Hardware Security -- How to Effectively Decrease the Resource Requirement in Template Attack? -- Deterministic Hard Fault Attack on Trivium (short paper) -- DPA Resilience of Rotation-Symmetric S-boxes -- A Technique using PUFs for protecting circuit layout designs against Reverse Engineering -- Hydra: An energy-efficient programmable cryptographic coprocessor supporting elliptic-curve pairings over fields of large characteristics -- Foundation.-On the Security Proof of an Authentication Protocol from Eurocrypt 2011 -- Improved Linear Cryptanalysis of Reduced-Round MIBS -- Characterization of EME with Linear Mixing -- Exponentiation inversion problem reduced from fixed argument pairing inversion on twistable Ate pairing and its difficulty (short paper) -- Encryption -- Related Key Secure PKE from Hash Proof Systems -- Towards Symmetric Functional Encryption for Regular Languages with Predicate Privacy (short paper) -- Framework for Efficient Search and Statistics Computation on Encrypted Cloud Data (short paper).
Keywords: Computer science; Computer security; Data encryption (Computer science).; Computer Science; Systems and Data Security; Data Encryption; Electronic books